Type 2 diabetes and Change in Total Hip Bone Area and Bone Mineral Density in Elderly Swedish Men and Women: Supplementary material - Mitchell, Adam; Fall, Tove; Melhus, Håkan; Lind, Lars; Michaëlsson, Karl; Byberg, Liisa (Uppsala University, 2021)
Supporting data to the manuscript "Type 2 diabetes and Change in Total Hip Bone Area and Bone Mineral Density in Elderly Swedish Men and Women"

In SMCC, Fasting plasma glucose concentrations were analysed using three different methods depending on date of collection; glucose dehydrogenase reagent (Bergman & Beving, instrument Advia 1650, Stockholm, Sweden), glucose oxidase method (Bayer, instrument Advia 1650, Leverkusen, Germany), and hexokinase method (Abbott, Abbott Architect, Illinois, USA).

In PIVUS, fasting plasma glucose concentrations were analysed using the standard method at Uppsala University Hospital.

In ULSAM, fasting plasma glucose concentrations (mmol/l) were measured by the glucose dehydrogenase method (Gluc-DH, Merck, Darmstadt, Germany).

The dataset was originally published in DiVA and moved to SND in 2024.

Supporting data to the manuscript "Type 2 diabetes and Change in Total Hip Bone Area and Bone Mineral Density in Elderly Swedish Men and Women"

Se engelsk beskrivning för mer information.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Type 2 diabetes and Change in Total Hip Bone Area and Bone Mineral Density in Elderly Swedish Men and Women: Supplementary material
Keywords: Medical Science; Medicinsk vetenskap; Epidemiology; Epidemiologi; Orthopaedics; Ortopedi